The Direction of Development of Indonesian Contemporary and Experimental Music in the Millennium Era - Bratakusumah, Vari Vania (Indonesian Scientific Publication, 2023)
This research delves into the development trajectory of contemporary and experimental Indonesian music within the context of the millennium era. Grounded in the rich tapestry of Indonesia's cultural and musical heritage, this study employs a comprehensive analysis to explore the multifaceted dimensions that have shaped the evolution of these genres. The methodology encompasses a qualitative approach, utilizing interviews with prominent figures in the Indonesian music scene, archival research, and content analysis of relevant documents. By adopting this methodological framework, the study aims to unravel the underlying patterns, challenges, and opportunities that have marked the course of contemporary and experimental music in Indonesia. The results of this research contribute to the existing body of knowledge in music studies by shedding light on the dynamic interactions between artistic expression, cultural identity, and governmental interventions. Furthermore, the study identifies key trends and emerging paradigms, providing valuable insights for scholars, practitioners, and policymakers involved in promoting and preserving Indonesia's musical heritage. In conclusion, this study offers a nuanced understanding of the direction of development in Indonesian contemporary and experimental music in the millennium era. By bridging the domains of social science and the arts, it seeks to contribute to a more profound appreciation of the intricate dynamics that shape the cultural landscape of Indonesia, fostering a conducive environment for the continued flourishing of its diverse musical expressions.